Dosimetry is Key to Good Epidemiology: Workers at Mallinckrodt Chemical Works had Seven Different Source Exposures. Issue 4 (April 2018) - Ellis, Elizabeth D.; Boice, John D.; Golden, Ashley P.; Girardi, David J.; Cohen, Sarah S.; Mumma, Michael T.; Shore, Roy E.; Leggett, Richard W.; Kerr, George D.
Abstract : Abstract: Mallinckrodt Chemical Works was the earliest uranium processing facility in the Manhattan Project, beginning in 1942. Even then, concern existed about possible health effects resulting from exposure to radiation and pitchblende dust. This concern was well founded as the facility processed Belgian Congo pitchblende ore that was up to 60% pure uranium with high 235 U content and up to 100 mg of radium per ton. Workers were exposed to external gamma radiation plus internal radiation from inhalation and ingestion of pitchblende dust (uranium, radium, and silica). Multiple sources of exposure were available for organ dose reconstruction to a degree unique for an epidemiologic study. Personal film badge measures available from 1945 captured external exposures. Additional external exposure included 15, 518 occupational medical x-rays and 210 radiation exposure records from other facilities outside of Mallinckrodt employment. Organ dose calculations considered organ-specific coefficients that account for photon energy and job-specific orientation of workers to the radiation source during processing. Intakes of uranium and radium were based on 39, 451 uranium urine bioassays and 2, 341 breath radon measurements, and International Commission on Radiological Protection (ICRP) Publication 68 biokinetic models were used to estimate organ-specific radiation absorbed dose. Estimates of exposure to airborne radon and its short-lived progeny were based on radon measurements in work areas where radium-containing materials were handled or stored, together with estimated exposure times in these areas based on job titles. Dose estimates for radon and its short-lived progeny were based on models and methods recently recommended in ICRP Publication 137. This comprehensive dosimetric approach follows methods outlined by the National Council on Radiation Protection Scientific Committee 6‐9 for the Million Worker Study. Annual doses were calculated for six organs: lung, brain, heart, kidney, colon and red bone marrow. Evaluation and adjustment for individual cumulative measures of pitchblende dust inhalation were made for lung and kidney diseases.